Identification of New Bioactive Compounds by Gc Ms and Estimation of Physiological and Biological Activity of Kala Dhaman Cenchrus setigerus - Singariya, P (International Journal of Pharmaceutical & Biological Archive, 2012)
Identification of New Bioactive Compounds by Gc Ms and Estimation of Physiological and Biological Activity of Kala Dhaman Cenchrus setigerus